Peningkatan Pemahaman Green Supply Chain untuk Konstruksi Bandara bagi Siswa SMK - Arifai, Achmad Muhyidin; Priansyah, Deni (Jurnal Abdimas Transportasi & Logistik, 2025)
The construction of transportation infrastructure, such as airports, poses significant challenges in terms of environmental sustainability. Therefore, introducing the concept of Green Supply Chain (GSC) to vocational high school (SMK) students in the logistics field is essential. This community service activity aimed to improve students' understanding of GSC through interactive training and structured evaluation. The implementation method included the delivery of materials, discussions, and pre-test and post-test assessments to measure the effectiveness of the activity. The results showed a significant increase in students' comprehension, with the average pre-test score of 73 rising to 88 in the post-test. The N-Gain score of 0.5556 categorized the training as moderately effective. This activity contributed to equipping SMK students with environmental awareness related to construction practices and supported the integration of sustainability topics into vocational education. The outcomes also indicate that such training has strong potential for further development into more contextual and applicable learning models for vocational students.